Gender Equality in the Early Twentieth Century: A Historical Analysis of Peranakan Chinese Literary Works in Doenia Baroe (1930) - Sari, Risa Junita; Samry, Wannofri (Andalas International Journal of Socio-Humanities, 2025)
This study examines representations of gender equality in Peranakan Chinese literary works published in the newspaper Doenia Baroe in 1930. As a medium that provided a relatively broad space for expression and social imagination, Doenia Baroe became an essential platform for Peranakan Chinese women in the Dutch East Indies, who stood at the crossroads between conservative Chinese traditions and the expanding influence of Western modernity. Through formal education—both in Tiong Hoa Hwee Koan (THHK) schools and Western-style schools—a group of educated women emerged who began to recognize and question the inequality of gender roles. Employing historical research methods, including heuristics, source criticism, interpretation, and historiography, and integrating a gender theory approach, this study analyzes how literary works functioned as a medium for critique, proposed solutions, and reflections on women’s struggles against cultural constraints. The findings indicate that female characters in these works display a growing awareness of the importance of education, freedom in choosing life partners, personal independence, and the courage to enter the public sphere. In addition, the authors frequently portray tragic consequences as moral warnings that highlight tensions between tradition and modernity. Overall, the representation of gender equality in Peranakan Chinese literature reflects broader social dynamics and underscores the role of literature as a significant arena for women’s ideological struggles against gender injustice in the Dutch East Indies during the early twentieth century.